Uranium mineralization indicators from seismic and well log data in the Shea Creek area at the southern margin of the Carswell impact structure, Athabasca Basin, Canada. (22nd June 2015) - Hajnal, Z.; Takacs, E.; Pandit, B.; Annesley, I.R.
ABSTRACT: The primary economic uranium (U) mineralization indicators in the Athabasca Basin are the reactivated prominent basement deformation zones, basement alteration halos, and the overlying sandstone alteration halos enveloping the deposit. High‐resolution seismic surveys, from the Shea Creek area, are investigated to assess the potential of the surface seismic reflection technique for detecting these key mineralization markers. Four seismic profiles identify ductile to highly brittle deformation features of the basement. One of the brittle deformation features is a southwest‐dipping prominent reactivated shear zone comparable to basement structures hosting other known deposits in the basin. The Carswell meteor impact structure is also a conspicuous component of the Shea Creek regional structural regime. The seismic sections identify several features of the impact structure, including recognition that the dimensions of this structure are significantly larger than those estimated by previous geological studies. This larger area includes both the Cluff Lake mine and the Shea Creek U deposits, and it reveals that the basement was considerably disturbed by the impact and suggests the reactivation of the southwest‐dipping shear zone. Complex trace analysis of the seismic sections provides detailed information about the lateral changes in the reflectivity properties of the unconformity interval, which is another key zone of interest for uranium exploration. Based mainly on velocity information, several sub‐zones of clay alteration and silicification were identified within prominent fracture depth intervals: both in the sandstone and the basement. Thus, this study documents that these primary mineral indicators can be detected by the seismic method. Cross‐plots of velocity versus density of well log data identify changes in lithological units such as unaltered basement, fractured/altered basement, unaltered sandstone, clay alterations in sandstone, and silicification in sandstone.